Religions by Continent - Johnson, Todd M. (Journal of religion and demography, 2022)
To supplement our global assessment of 18 religions in a previous article in this issue of the journal, here we offer analysis of religious affiliation by the globe and six continents: Africa, Asia, Europe, Latin America, Northern America, and Oceania. Estimates of religious affiliation are made for four dates, 1970, 2000, 2022, and projections for 2030. We also contrast growth in two 30-year periods, 1970–2000 and 2000–2030. These global and continental tables are based on country data (World Religion Database). United Nations regional tables (e.g., Western Africa) can also be constructed from the country data.